DNA Methylation Status of the RETN and ADIPOQ Genes in Sporadic Colon Cancer - Al-Harithy, Rowyda N; Abdulsalam, Eman A Al (Archives of Clinical and Biomedical Research, 2024)
Background: Colon cancer develops through a complex process that involves epigenetic alterations. Compelling evidence has been achieved that adipocytokines link obesity with colon cancer progression. Therefore, understanding the epigenetic modifications in adipokine genes might help clarify their role in colon cancer pathogenesis. The present project aimed to study the DNA methylation status of the RETN and ADIPOQ genes in sporadic colon cancer patients. Methods: 70 cancerous colon tissues and adjacent paired non-cancerous tissues were used to determine the DNA methylation status using a methylation-specific polymerase chain reaction (MS-PCR) assay. Quantitative real-time PCR (qRT-PCR) was used to determine the expression level of the RETN and ADIPOQ genes. Results: In colon cancer tissues, the CpG sites in the three selected promoter regions of ADIPOQ and RETN genes were hypermethylated in all samples. The DNA methylation level at the CpG sites in exon one of the RETN gene exhibited a lower level in the non-cancerous tissue compared to the cancerous tissue and paired blood samples. The RETN mRNA was upregulated. Conclusion: Our study indicates that hypermethylation at the CpG sites in the two regions of the ADIPOQ promoter and in exon one of the RETN genes might help uncover cancer signatures in sporadic colon cancer and may be used as a biomarker.